Freedom of Contract in the Digital Age: Perspectives on the Indonesian Civil Code and Fiqh Muamalah - Shoimah, Siti Nur (Faculty of Law Universitas Trunojoyo Madura, 2026)
This study examines the urgency of reconstructing the principle of freedom of contract in electronic contracts through a dialectical analysis between Article 1338 of the Indonesian Civil Code and the normative framework of fiqh muamalah. This reconstruction is crucial in the context of standard-form and digital contracts, which tend to place one party in a weaker bargaining position and expose it to unilateral clauses. The study aims to formulate a more equitable and ethically grounded conception of contractual freedom that can respond to contemporary commercial practices, particularly electronic and hybrid contracts. This article contributes to the development of contract law theory by integrating civil law rationality with Islamic legal values to address structural imbalances in contractual relations. Employing a doctrinal legal research method, this study applies statutory, conceptual, and comparative approaches, including an analysis of constitutional jurisprudence. The findings demonstrate that a formalistic application of the principle of freedom of contract often legitimizes inequality and weakens protections for disadvantaged parties, especially in standard-form contracts. These limitations are reinforced by Constitutional Court Decision No. 83/PUU-XXII/2024, which declared Article 251 of the Commercial Code (KUHD) on the unilateral termination of insurance contracts conditionally unconstitutional and affirmed that contract termination must be based on mutual consent or a court decision. Based on these findings, this study proposes a reconstructed model of freedom of contract encompassing substantive justice, an orientation toward maslahah (social welfare), and ethical contractual morality grounded in good faith and honesty. The study concludes that harmonizing the Indonesian Civil Code with fiqh muamalah, strengthened by constitutional justice, produces a more balanced, transparent, and welfare-oriented contractual framework without undermining contractual autonomy.